Comparison of Earthworm (Lumbricidae) and Oribatid Mite (Acari, Oribatida) Communities in Natural and Urban Ecosystems - Murvanidze, M.; Kvavadze, E.; Mumladze, L.; Arabuli, T. (Вестник зоологии, 2011)
This study investigates earthworm and oribatid mite communities in urban, semi-natural and natural ecosystems of Tbilisi (Georgia). Ten species of earthworms and 100 species of oribatid mites were registered in 45 soil samples. Two species of oribatid mites, Microzetes auxilaris Grandjean, 1936 and Multioppia laniseta Moritz, 1966, are new for the Caucasian fauna. We hypothesized that species number and abundance of invertebrate animals tend to decrease from natural to urban ecosystems. The hypothesis was supported only partially. Number of species of oribatid mites and earthworms decreased together with increase of urbanization, whereas abundance showed no significant changes due to high density of stress tolerant and ubiquitous species in urban sites. Accordingly, species abundance is considered to have minor indicatory value. Our studies support ecological “time-hypothesis” in a way that older (natural) sites were presented with more diverse fauna than recent (urban) ones. Statistical analyses showed that studied ecosystems should be grouped in two rather than three categories: in urban and natural ones.